PENGARUH AKUNTABILITAS DAN KOMPETENSI AUDITOR/PENGAWAS PEMERINTAH TERHADAP KUALITAS AUDIT - Ohoimas, Endang Sri Rahayu; Salle, Agustinus; Daat, Sylvia Christina (Fakultas Ekonomi, Universitas Cenderawasih, 2018)
Auditors’ decision making is affected by their accountability in concluding their audit working process that required highly competences which can be gained through their sufficient experiences in the audit field. This research is aim to examine the influence of accountability and competence of auditors/government supervisory on the quality of audit. As population in this research is 47 people of Employees who work in Provincial Inspectorate Office of Papua and Inspectorate office of Jayapura City which involved in the examination as the Auditors/Supervisory of Government. A non-probability sampling methodology is used based on the certain criteria (purposive sampling) for distributing 47 questionnaires to the Auditors/Supervisory of Government. The result of this research indicate that the devotion in profession has a significant effect on the quality of audit, while social obligation has a significant effect on the quality of audit. Similarly, the knowledge and working experiences have significant effects on the quality of an audit respectively.